Industrial/organizational psychology and the law: expert witness testimony and the federal judiciary - Wingate, Peter Hale, author; Thornton, George C., III, advisor; Bell, Paul, committee member; Cawley, Brian, committee member; Hogler, Ray, committee member (Colorado State University. Libraries, 2002)
This research examined judicial perceptions of the field of industrial/organizational (I/O) psychology, explored how judges evaluate and weigh VO psychology expert witness testimony, and scrutinized the use of the Daubert criteria in judicial assessments of social scientific evidentiary reliability. In a mail survey, active United States federal district, senior district, and magistrate judges were presented with prototypical descriptions of I/O psychology expert witness testimony in civil age discrimination in employment litigation. Judges were randomly assigned to 4 expert witness scenarios, which systematically varied the foundation and content of the expert’s testimony according to the Daubert criteria.

Judges were found to be relatively unfamiliar with the field of I/O psychology, and few had previously heard or read the testimony of an I/O psychologist. Sixty-six percent of the federal judges rated themselves at least moderately likely to admit the expert’s testimony at trial, regardless of the testimony scenario presented. Nineteen percent of the judges asserted that they were not at all likely to admit the expert’s testimony. Judges rated the evidence overall as relevant, moderately reliable, moderately probative, and prejudicial. Both judicial familiarity with the field of I/O psychology and prior experience with I/O testimony were found to be positively related to likelihood of admitting the evidence. Manipulations of the scientific foundation for the expert testimony did not significantly affect admittance decision. Judges ascribed the most importance to the general acceptance Daubert criterion in their evaluation of evidentiary reliability. Written comments provided by judges provided insight into rationales for inclusion or exclusion of the expert evidence, detailed perceptions relating to the field of I/O psychology, and elaborated on the Daubert standard’s applicability to social scientific evidence. Implications for the science and practice of I/O psychology in the legal system are presented, and practical suggestions for I/O psychologist expert witnesses are discussed.
Keywords: law